Maternal serum irisin levels in normotensive and preeclamptic pregnancies: a systematic review and meta-analysis . (3rd April 2022) - Vivek, Kumar; Thangappazham, Balachandar; Vykunta, Alekya; Kulkarni, Paresh P.; Pérez-López, Faustino R.; Varikasuvu, Seshadri Reddy
Abstract: Background: Altered irisin levels have been reported in pregnancy-associated disorders, such as preeclampsia. Objective: A systematic review and meta-analysis were conducted to evaluate the changes in maternal circulatory irisin levels in preeclampsia as compared to normotensive healthy pregnant controls. Methods: Relevant studies were identified by searching PubMed and other databases. Random-effects model was used to obtain standardized mean differences (SMDs) and its 95% confidence intervals (CIs). The sub-group meta-regression analyses were conducted to explore heterogeneity. The presence of publication bias and the study robustness was tested using funnel plot and sensitivity analyses, respectively. Results: This meta-analysis finally included 14 observations from eight studies. Compared with controls, preeclampsia patients showed significantly decreased serum irisin levels (SMD: −1.13; 95% CI: −1.63 to −0.62, p  < .0001). The sub-group analysis showed that this decrease in irisin is regardless of body mass index (BMI) and gestational age of preeclampsia patients. The meta-regression analysis indicated that blood pressure is significantly associated with the observed results. There was no significant publication bias as indicated by the funnel plot analysis followed by Begg's ( p  = .35) and Egger's tests ( p  = .39). The sensitivity analysis indicated that no single study had a significant influence on the overall outcome, suggesting the robustness of this meta-analysis. Conclusions: This meta-analysis showed significantly decreased maternal serum irisin level in preeclampsia patients as compared to normotensive pregnant women. This study highlights the need for future studies evaluating the diagnostic utilities and associations of irisin with the fetal and neonatal outcomes in preeclampsia.